2021
DOI: 10.1111/1471-0307.12784
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation, validation and comparison of methods for aflatoxin M1 determination in cheese

Abstract: Accurate and reliable determination of aflatoxins in food is important for human health. There is no standard method for the determination of aflatoxin M1 (AFM1) in cheese, a more complex matrix, compared with milk. In this research, we applied two analytical detection techniques (a standard accredited HPLC method for AFM1 in milk and a commercial ELISA method), with three extraction methods, on two different cheese matrices, with repeated tests and appropriate statistical analysis. The examined methods were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…There is also evidence that AFB1 has an equally significant or higher effect on the cell function and integrity by inducing oxidative stress (OS) (Benkerroum, 2020;Omara et al, 2020). Aflatoxin M1 is a mammalian hydroxylated metabolite of AFB1 excreted through urine and has been classified as a possible human carcinogen in breast milk (Group 2B) (Misihairabgwi et al, 2019;International Agency for Research on Cancer, 2012;Pimpitak et al, 2020;Abdullah Murshed et al, 2022;Jakšić et al, 2021). Studies have shown that the effect of AFB1 and AFM1-induced injury and its ability to induce cancer initiation is related to a group of genes/proteins/miRNAs (Bilandžić et al, 2022;Marchese et al, 2018).The decline in aflatoxin levels depends on the combination of time and temperature and is not affected by fermentation.…”
Section: Aflatoxinmentioning
confidence: 99%
“…There is also evidence that AFB1 has an equally significant or higher effect on the cell function and integrity by inducing oxidative stress (OS) (Benkerroum, 2020;Omara et al, 2020). Aflatoxin M1 is a mammalian hydroxylated metabolite of AFB1 excreted through urine and has been classified as a possible human carcinogen in breast milk (Group 2B) (Misihairabgwi et al, 2019;International Agency for Research on Cancer, 2012;Pimpitak et al, 2020;Abdullah Murshed et al, 2022;Jakšić et al, 2021). Studies have shown that the effect of AFB1 and AFM1-induced injury and its ability to induce cancer initiation is related to a group of genes/proteins/miRNAs (Bilandžić et al, 2022;Marchese et al, 2018).The decline in aflatoxin levels depends on the combination of time and temperature and is not affected by fermentation.…”
Section: Aflatoxinmentioning
confidence: 99%